2013
DOI: 10.1681/asn.2012050490
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the Ciliary Kinase Nek8 Causes Left-Right Asymmetry Defects

Abstract: A missense mutation in mouse Nek8, which encodes a ciliary kinase, produces the juvenile cystic kidneys (jck) model of polycystic kidney disease, but the functions of Nek8 are incompletely understood. Here, we generated a Nek8-null allele and found that homozygous mutant mice die at birth and exhibit randomization of left-right asymmetry, cardiac anomalies, and glomerular kidney cysts. The requirement for Nek8 in left-right patterning is conserved, as knockdown of the zebrafish ortholog caused randomized heart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
46
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 74 publications
3
46
0
1
Order By: Relevance
“…In mammals, mutations affecting NEK8/NEKL-2, ANKS6/MLT-2, INVS/MLT-4, and ANKS3/MLT-3 have been directly linked to a class of diseases termed ciliopathies, which result from defects in the formation of primary cilia Otto et al 2008Otto et al , 2011Trapp et al 2008;Halbritter et al 2013;Hoff et al 2013;Delestre et al 2015). These include kidney disorders, such as nephronophthisis type 2 (Otto et al 2003) and juvenile cystic kidney disease (Liu et al 2002), as well as situs inversus, cardiovascular abnormalities, liver fibrosis, and defects in other organ systems Hoff et al 2013;Manning et al 2013). These findings, as well as the expression of NEK8, INVS, ANKS6, and ANKS3 in the proximal ciliary compartment (Shiba et al 2009(Shiba et al , 2010Hoff et al 2013;Delestre et al 2015), have led to the view that these proteins function primarily to control cilia formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mammals, mutations affecting NEK8/NEKL-2, ANKS6/MLT-2, INVS/MLT-4, and ANKS3/MLT-3 have been directly linked to a class of diseases termed ciliopathies, which result from defects in the formation of primary cilia Otto et al 2008Otto et al , 2011Trapp et al 2008;Halbritter et al 2013;Hoff et al 2013;Delestre et al 2015). These include kidney disorders, such as nephronophthisis type 2 (Otto et al 2003) and juvenile cystic kidney disease (Liu et al 2002), as well as situs inversus, cardiovascular abnormalities, liver fibrosis, and defects in other organ systems Hoff et al 2013;Manning et al 2013). These findings, as well as the expression of NEK8, INVS, ANKS6, and ANKS3 in the proximal ciliary compartment (Shiba et al 2009(Shiba et al , 2010Hoff et al 2013;Delestre et al 2015), have led to the view that these proteins function primarily to control cilia formation.…”
Section: Discussionmentioning
confidence: 99%
“…NEKL-2 is orthologous to mammalian NEK8, which has been implicated in ciliogenesis Quarmby and Mahjoub 2005;Otto et al 2008;Shiba et al 2010;Zalli et al 2012). Correspondingly, mutations in NEK8 can lead to organogenesis defects resulting from ciliopathies Otto et al 2008Otto et al , 2011Trapp et al 2008;McCooke et al 2012;Halbritter et al 2013;Hoff et al 2013;Manning et al 2013;Delestre et al 2015). NEKL-3 is the C. elegans ortholog of mammalian paralogs NEK6 and NEK7, which have been reported to control several processes associated with cell division and are linked to human cancer.…”
mentioning
confidence: 99%
“…Therefore, in a human patient with a mutation in PC2, their cilia will not signal flow information appropriately, which will lead to disease. The jck (juvenile cystic kidneys) mouse model for PKD is defective in Nek8, a PC2-interacting kinase, and it has been shown that this kinase is also required for sensing fluid shear forces (Manning et al 2013), which further supports the link between force sensing and PKD. Although we think of this disease as resulting from a failure of cilia to detect forces acting on them, this may also be a case in which forces acting on the tissue can influence formation of cilia.…”
Section: Ciliopathies and Mechanicsmentioning
confidence: 86%
“…Quand la kinase ciliaire Nek8 (NIMA-related kinase 8) est mutée, les cils se forment normalement. Cependant, l'orientation de la courbure du coeur se fait au hasard chez ces mutants, qui présentent aussi des défauts de cloisonnement des chambres cardiaques et un ventricule droit à double issue [22]. Dans ces modèles animaux, l'inactivation génétique est zygotique, c'est-à-dire ubiquitaire, ce qui ne permet pas de comprendre dans quels types cellulaires les cils sont requis.…”
Section: Signalisation Droite/gauche Et Alignement Des Chambres Cardiunclassified